Sustainable in Action: From Intention to Environmentally Friendly Practices in Makerspaces Based on the Theory of Reasoned Action - Klemichen, Antje; Peters, Ina; Stark, Rainer (Frontiers in Sustainability, 2022)
The steady growth of makerspaces to decentralized production enables access to new and previously unknown technologies for diverse users and thus equally promotes the social-ecological change in society. First, such facilities offer a physical space where ideas and innovations can be realized as prototypes or in small series. Secondly, they are also considered social spaces where people come together, exchange ideas, work collaboratively and learn. The acquired knowledge is carried home and into peer groups outside the makerspaces. Therefore, in theory the maker scene has great potential for sustainable development especially in the educational and awareness raising context. However, there is a strong heterogeneity among makers not only in their intentions to use such places, but also in their educational background and experience in product development as well as in dealing with technology in general. It has been shown that makers certainly have an awareness of the need for sustainable development, however, this is not reflected in their actual making practices. Rather, makerspaces are characterized by high consumption of resources. A fundamental aspect here is the self-image of makers, in which sustainability plays a subordinate role. It is thus important to support individual production, which is associated with increasing consumption of resources in the early design phase, and to consider environmental aspects - even before 3D printers and laser cutters are switched on. In order to meet knowledge gaps and lack of motivation towards sustainable product creation, the ecoMaker project developed an approach for a holistic concept in makerspaces which is to build the bridge from knowledge to action. The Theory of Reasoned Action is combined with engineering and sustainability knowledge and transferred into tools and methods for the maker scene based on their needs and requirements. Those tools and methods intend to be visible at various places in the makerspace and at different stages of their project idea to help them develop greener products and raise awareness of the makerspace as a place that promotes sustainable development. The elements have been co-developed with makers, applied in makerspaces and are freely available according to the open-source approach.